THE EFFECTS OF N-FERTILIZER RATE ON THE PHYSIOLOGY AND THE YIELD OF SOYBEAN (GLYCINE MAX (L.) MERR.) UNDER DIFFERENT IRRIGATION REGIMES - Basal, Oqba; Szabó, András (LIFE: International Journal of Health and Life-Sciences, 2018)
Global Climatic changes are being more and more obvious, resulting in massive fluctuations in the food availability for the increasing world population because of the abiotic stresses resulted from these changes, with drought stress being one of the most serious stresses. Using mineral fertilization was introduced as a proposed solution to overcome the food gap resulted from the above-mentioned factors, but the negative effects of the mineral fertilization on both soil environment and food quality makes it necessary to come out with alternative solutions. Legume crops are able to fix atmospheric nitrogen by the symbiosis process, which reduces the need of mineral N. Soybean is one of the most important legumes with its high content of protein and oil, but is drought-susceptible. An experiment was conducted to investigate the effects of both drought stress and mineral N on the physiology and the yield of two soybean cultivars during 2017 growing season. The results showed that applying N-fertilizer enhanced the physiology of soybean plants, especially under drought conditions; yet, high rates of N-fertilizer did not result in better yield. It was concluded that the effects of drought stress on soybean are more serious and obvious than of the N fertilization. In addition, adding high rates of N-fertilizer is not always favorable, especially with the absence of drought stress conditions.